2019
DOI: 10.1038/s41598-018-36720-6
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the bladder cancer precursor urothelial hyperplasia requires FOXA1 and persistent expression of oncogenic HRAS

Abstract: Tumorigenesis requires accumulation of genetic and epigenetic alterations, some of which drive tumor initiation. “Oncogene addiction” describes the phenomenon that (1) well-established cancers are dependent on one mutated oncogene or pathway for the maintenance of a malignant phenotype and that (2) withdrawal of the single oncogenic event leads to growth arrest and/or cancer regression. While oncogene addiction has been experimentally validated in advanced tumor models, its role in tumor precursors has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In the present study, we also found high levels of KRT14 EMT gene expression in LCNEC compared to AC, as well as high levels of MAP1B in SCLC. These EMT genes are involved in phenotypic changes related to the dimension and stability of the cytoskeleton during tumorigenesis [ 43 ]. Their expression may minimize the known difficulty to separate LCNEC from SCLC, as well as AC from LCNEC and AC from SCLC in terms of cell dimension [ 44 ], with significant interobserver variation and biological similarities contributing to this aspect [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also found high levels of KRT14 EMT gene expression in LCNEC compared to AC, as well as high levels of MAP1B in SCLC. These EMT genes are involved in phenotypic changes related to the dimension and stability of the cytoskeleton during tumorigenesis [ 43 ]. Their expression may minimize the known difficulty to separate LCNEC from SCLC, as well as AC from LCNEC and AC from SCLC in terms of cell dimension [ 44 ], with significant interobserver variation and biological similarities contributing to this aspect [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that FOXA1 is a luminal marker and prognostic biomarker in BCa [ 50 , 51 ], and a lack of nuclear expression for FOXA1 could be regarded as basal-like MIBC [ 52 ]. Continuous expression of FOXA1 can lead to a marked reduction in urothelial proliferation [ 53 ]. However, the detailed mechanisms of FOXA1 in regulating BCa metastasis are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In BC cell lines, studies by others have shown that have shown that GATA3 and FOXA1 cooperate with PPARγ activation to drive the differentiation of a basal bladder cancer subtype to a more differentiated luminal subtype [ 23 ]. Other studies have also linked the expression of FOXA1 to the development of the luminal subtype of urothelial cancer [ 42 44 ]. In our studies, treatment with TG did result in the differentiation of the As 3+ -transformed cells based upon morphological changes and induced the expression of PPARγ as well as FOXA1 both of which are factors known to drive luminal differentiation of bladder cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%